1987
DOI: 10.1039/f19878301559
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical formation of colloidal metals

Abstract: Colloidal silver and gold have been formed by irradiation of AgC10, and HAuC1, solutions with 253.7 nm light in the presence of protective agents such as sodium dodecylsulphate, sodium alginate and colloidal silica. Absorption maxima of colloidal silver and gold have been observed at 390-420 and 540-560 nm, respectively. Colloidal metals have been purified by dialysis and their amounts analysed quantitatively. The quantum yields of metal deposition are 0.053-0.15 for colloidal silver and 0.030-0.039 for colloi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
43
0
3

Year Published

1988
1988
2005
2005

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 104 publications
(49 citation statements)
references
References 0 publications
3
43
0
3
Order By: Relevance
“…Photolysis of the solutions and quantitative analysis of deposited silver and gold were carried out as described in previous paper. 5 The light source (a 200 W low-pressure mercury lamp) and the reaction cell (a rectangular quartz vessel of 1 cm x 1 cm x 4 cm in size) were as before. The cell was set up in a dark box and 3.5cm3 of aqueous sodium alginate solution (0.2 wt YO) containing AgClO, and/or HAuC1, was placed in it for photolysis.…”
Section: Methodsmentioning
confidence: 99%
“…Photolysis of the solutions and quantitative analysis of deposited silver and gold were carried out as described in previous paper. 5 The light source (a 200 W low-pressure mercury lamp) and the reaction cell (a rectangular quartz vessel of 1 cm x 1 cm x 4 cm in size) were as before. The cell was set up in a dark box and 3.5cm3 of aqueous sodium alginate solution (0.2 wt YO) containing AgClO, and/or HAuC1, was placed in it for photolysis.…”
Section: Methodsmentioning
confidence: 99%
“…Typically, the absorption maximum for the SPR peak of Ag nanoparticles in films are observed at 410 nm. 6,[8][9][10][11][12] Accordingly, the observance of SPR peaks indicated that the size of the Ag nanoparticles are much smaller than the mean free path of the electrons in bulk silver (ca. 52 nm), 20 as shown in Figure 2.…”
Section: Nylon 6/ag Compositesmentioning
confidence: 99%
“…6,8,9 Similarly as that of Au nanoparticles, it is well known that Ag nanoparticles possess interesting optical properties: for example, surface plasmon resonance (SPR) in the state of nanoparticle. 6,[8][9][10][11][12] Additionally, Ag nanoparticles in nylon 11/Ag can be converted into Ag 2 S nanoparticles by exposing to a mix- † To whom correspondence should be addressed.…”
mentioning
confidence: 99%
“…The photochemical method for the creation of nanodimensional particles of silver in the colloid state has a number of advantages over other methods since it does not require complex apparatus and high temperatures. Irradiation of aqueous alcoholic solutions of silver ions in the presence of stabilizing agents, including water soluble polymers (sodium alginate), surfactant anions (sodium dodecylsulfate), and stabilized SiO 2 , TiO 2 , and ZnO colloids, led to the formation of nanoparticles of Ag [7]. It has been established [8] that introduction of aromatic ketones (acetophenone, benzophenone) into the reaction mixture led to an increase in the rate of photoreduction and sensitized the reaction to near UV radiation (355-365 nm).…”
mentioning
confidence: 99%
“…Starting from literature data on the absorption spectra of a large number of the products of photoreactions [6][7][8] and our results obtained previously on the emission and excitation spectra of BP [10], the following mechanism is proposed for the photoreduction of silver and the formation of nanoparticles: on irradiation with light with λ = 253.7 and 365 nm the BP molecule is converted into a reactive triplet state, capable of removing a hydrogen atom from aliphatic alcohols, to form two ketyl radicals. The latter undergo protolytic dissociation to form the anion-radical of BP and isopropanol, which has a high negative electrochemical potential and is capable of reducing noble metal cations [6].…”
mentioning
confidence: 99%